Multidisciplinary Study of Subsidence and Sinkhole Occurrences in the Acque Albule Basin (Roma, Italy). Issue 7 (10th July 2020) - De Ritis, R.; Nardi, A.; Materni, V.; Venuti, A.; Stefanelli, P.; Rotella, G.; Sapia, V.; Carpentieri, E.; Tolomei, C.; Civico, R.; Coltorti, M.; Nanni, T.; et al.
Abstract: We present the results of a combined analysis of remote sensing and geophysical‐geotechnical data carried out in the Acque Albule Basin, a sinkhole prone area located close to the city of Roma, where a wide travertine wedge is present. We carried out geophysical measurements and borehole drillings over two test areas to image the subsoil where paroxysmal surficial dynamics occur. One site is marked by subsidence occurring at least since the early 2000s, whereas the other site hosts the "La Regina" and "Colonnelle" sinkhole lakes, which discharge sulfur‐carbonated waters. The stability of these two sites threatens highway, railway, and airport facilities, and this study helps to assess the geological hazard. For example, InSAR and LiDAR data helped define wide scale subsidence over the last 20 years and previously undetected small‐scale morphologies. Geophysical measurements of the latter revealed shallow and deep dissolution affecting the travertine and driving surficial paroxysmal events. Both study sites were found to lie inside a large depression located at the junction between Jurassic carbonate and Plio‐Pleistocene units in association with paleo karst morphologies in the travertine deposits and affected by the present‐past spillage of sulfurous waters. Given these elements, multidisciplinary geophysical observations are crucial for assessing and mitigating the geological risk and guiding land use planning and management. Plain Language Summary: The Acque Albule Basin is a sinkhole prone area of carbonate rocks. The lithoid travertine has been quarried since the Etruscans time and represented the main building material during ancient Roman time ( Lapis Tiburtinus ). Currently, this region is actively mined and also exhibits frequent sinkhole activity. However, urban development has notably increased over the last decades, subjecting the infrastructure and population to high geologic risk and complicating effective geological and geophysical investigations due to the lack of access and anthropogenic noise. Thus, we used remote sensing to identify a wide subsiding sector involving also urban centers and a geophysical‐geotechnical study to assess the predisposing factors affecting the travertine and generating surficial paroxysmal events that may affect the farmlands and nearby cities. The integrated approach used in this study provides a guideline for geological risk assessment and rational urban planning. Key Points: Remote sensing and geophysical data map a wide regional subsiding sector in the Acque Albule Basin Complementary geophysical techniques combination Topography and travertine correlative features in highly dynamic geomorphological systems